2017
DOI: 10.3390/app7050451
|View full text |Cite
|
Sign up to set email alerts
|

Using Acoustic Emission Methods to Monitor Cement Composites during Setting and Hardening

Abstract: Cement-based composites belong among the basic building materials used in civil engineering. Their properties are given not only by their composition but also by their behaviour after mixing, as well as by the methods of curing. Monitoring the processes and phenomena during the early stages of setting is vital for determining the resulting properties and durability. The acoustic emission method is a unique non-destructive method that can detect structural changes as a cement-based composite is setting. It can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Table 1 shows the composition of composites. From each mixture, three test specimens with dimensions of 40 × 40 × 160 mm were manufactured and tested [16]. All specimens were coated with the PE foil during the hardening in laboratory conditions at a temperature of (21 ± 2)°C and relative humidity of (60 ± 10)% until the time of testing.…”
Section: Methodsmentioning
confidence: 99%
“…Table 1 shows the composition of composites. From each mixture, three test specimens with dimensions of 40 × 40 × 160 mm were manufactured and tested [16]. All specimens were coated with the PE foil during the hardening in laboratory conditions at a temperature of (21 ± 2)°C and relative humidity of (60 ± 10)% until the time of testing.…”
Section: Methodsmentioning
confidence: 99%
“…Some studies indicated start or peak of AE activity during the calorimetric temperature peak that implies relation to the hydration reaction [23][24][25]. However, other studies [26,27] showed the large majority of recorded hits occurring earlier than this peak, leading to the conclusion that significant processes (possibly of lower intensity and thus more difficult to register) occur from as early as the mixing time, much before the chemical reaction of hydration initiates and any heat is developed. Differences in the acquisition equipment (including sensor frequency range and sensitivity), the coupling (with or without waveguide) and the specimen size do not allow for robust conclusions relatively to the original sources.…”
Section: Acoustic Emission In Fresh Concretementioning
confidence: 99%
“…The acoustic emission method allows such an approach. The analysis of the recorded acoustic emission signals can be successfully used for a more detailed evaluation of the behaviour of the tested materials [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%